Narrativas amazônicas e novas tecnologias: diálogos possíveis na formação do leitor - SILVA, Ayholândia Moraes da (Universidade Federal do Pará, 2019)
Contributing to the student's reading and writing development and their insertion into society is what this work intends to do. Thus, the initial idea is a proposal of organized reading (and writing), mainly, from the orientation of the writings of Bakhtin / Volochinov (1992), Rossi's studies (2008) about the pedagogical project of reading and written production and Rojo (2012) on teaching of reading associated with new technologies and Amazonian culture. To do so, through participant research, we took into account the relevance of reading in human formation, the cultural repertoire and the cognitive ability of readers. This proposal was prepared for a group of 6th grade / 9 belonging to the public sphere of education. It is hoped, in this sense, to promote the formation of competent readers who are able to dialogue with the information that is present in the text they read to, based on this and the many technological tools that the postmodern world offers nowadays, the reader (like the example of the Wondershare Filmora program), produce their own stories. Within this proposal the reading (and writing) of Amazonian legends, such as "the legend of the great snake" and "the legend of the mother of water", is highlighted. The choice of texts was based on the pedagogical and cognitive possibilities that the genre has, and due to the proximity to the cultural context of which the student is part, as well as being stories inspired by the popular imagination that, when using a very attractive combination between the real and the fantasy world awaken the interest of the reader and, thereby, dynamize the process of teaching and learning.